The use of LP-RAPD for assessing genetic relatedness among selected banana cultivars - Daud, Siti Khalijah; Mohd Zaidi, Nor Salina; Mohd Fadzillah, Nor'Aini; Mahmood, Maziah (Universiti Putra Malaysia Press, 2006)
LP-RAPD (Long primer Random Amplified Polymorphic DNA) analysis was carried out on eight banana cultivars namely Mas (AA), Berangan (AAA), Raja (AAB), Rastali (AAB), Awak (ABB), Nipah (BBB), Kapas (AAB) and Nangka (AAB) to assess their genetic relationships. Twenty five individuals of each cultivar were collected from the Malaysian states of Perak, Selangor, Melaka and Negeri Sembilan. Five long-primers, namely PEH A3, ERICIR, PUCMI3F, BOXAIR and PEHA6were selected to amplify the genomic DNA. The DNA bandingpatterns were observed and analyzed. The results showed that the largest fragment was 2500 bp and the smallest 100 bp. The ERICIR was found to be the most polymorphic primer (26.5 %) whilst PEHA6 was the least polymorphic (20.8 %). The dendrogram revealed three major groups. Group I consisted of Berangan, Rastali, Mas, Nangka and Raja cultivars. Group II included Kapas and Awak, which had the lowest genetic distance (0.3633) and are known as plantains by sharing the B genotype. Groups I and II were clustered closely together with a genetic distance of 0.3961 indicating a close relationship between the two groups. The Nipah (BBB) cultivar alone was distinctly separated from both Groups I and II with a genetic distance of 0. 795. Although all cultivars differ morphologically, the findings agree with the degree of shared genotypes, A or B, among the cultivars.